A Transmission Method for Conductivity Extraction of Printed Silver Ink - Ehrngruber, Michael; Neermann, Simone; Gold, Gerald (IEEE, 2022)
This paper presents a measurement method being capable of characterizing impact from sintering on reached electrical conductivity of nano silver inks. Therefore, a measurement setup at relatively low frequencies was chosen, so that the electromagnetic (EM) field completely penetrates the conductive region. Thus, the transmission which is highly influenced by the conductivity variations of the material under test can be measured. Even small variations due to different sintering temperatures are measurable in this way. A model describing the transmission of the EM-field through the material sample including a carrier layer of polyimide was set up, which allows for inferring the conductivity of the sample. As samples sputtered copper layers are examined, as well as nano silver inks sintered at different temperatures and with different sintering methods.
Keywords: conductivity measurement; silver ink; material characterization; transmission; 3D printing

Generation of RF Structures on Additively Manufactured Substrates by Printed Electronics and Laser Structuring - Ankenbrand, Markus; Panusch, David; Utsch, Daniel; Banea, Kevin; Ehrngruber, Michael; Gold, Gerald; Helmreich, Klaus; Franke, Jörg (Proceedings of the SMTA Pan Pacific Microelectronics Symposium 2023, 2023)
In this work, printed electronics and laser processes are utilized to generate radio frequency (RF) structures for the X-band on additively manufactured substrates. The substrates are generated by Fused Filament Fabrication (FFF) with various materials. Conductive structures are applied with the processes Piezojet, Nanojet and Laser Direct Structuring (LDS). Piezojet is a drop-on-demand inkjet process that can print a wide range of inks and pastes with viscosities up to 200,000 mPas. Typical line widths are in the range of 300 - 500 μm. Nanojet uses ultra-sonic atomization to create an aerosol from a functional ink. In the nozzle, the aerosol is focused by an additional gas flow, which enables line widths as fine as 20 μm. Both Piezojet and Nanojet require a post-treatment step to dry or sinter the applied inks in order to achieve full conductivity. The LDS process works with a laser-activatable additive that is compounded into the material. Circuit tracks are generated by laser-scanning the layout on the substrate surface. The areas activated in this process are then metallized in an electroless plating process to achieve conducting paths. Moreover, the LDS-laser can also be used to smoothen the 3D-printed substrate surfaces and for sintering and trimming the circuits printed with Piezojet and Nanojet. In order to evaluate the different process and material combinations, the following coplanar structures are printed on additively manufactured substrates: Transmission line sections, a bandpass and a resonator. A network analyzer is used to measure the scattering parameters of the printed structures. With the measured magnitude and phase together with the geometry of the lines, an estimation for the relative permittivity εr can be obtained. This parameter is later used in the design process of an additively manufactured helix antenna. This antenna type offers a small form factor in combination with high gain and bandwidth, while radiating a signal of circular polarization. Many RF applications like satellite communication or radar imaging rely on circular polarized antennas [1,2]. The helix antenna is manufactured with the above-described processes in a 5-axis motion syste
Keywords: Additive Manufacturing; Printed Electronics; Microwave Technology; Mechatronic Integrated Devices; Helix antenna; X-band

Investigation of the effects of energy density in Laser Sintering of polypropylene on morphological and dielectric properties for high-frequency antennas - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Procedia CIRP, 2024)
Advancements in the Internet of Things demand more capable antenna systems, which benefit from the complex geometries enabled by additive manufacturing. Novel approaches, such as external metallization of polymers, enable the design of these geometries but require the processing of low dielectric-loss polymers in additive manufacturing. Arising from prevailing limitations on additively manufactured low-loss components, this study investigates the effect of energy density on polypropylene's dielectric properties in powder bed fusion processes. Variations in laser power significantly influenced material density and mechanical characteristics. Both insufficient and excessive energy densities resulted in lower quality parts due to issues like fused particles or inadequate melting. Optimal dimensional accuracy and surface quality were achieved with energy levels slightly below those for peak density. While dielectric loss remained mostly stable, relative permittivity decreased at very low densities, where partial melting occurred. Relying on derived optimized parameters, the functionality of passive high-frequency components was demonstrated.
CRIS-Team Scopus Importer:2024-09-27
Keywords: high-frequency antenna; Laser Sintering (SLS); polypropylene

Laser-Sintering of Cyclic Olefine Copolymer for Low Dielectric Loss Applications - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Polymers, 2024)
With increasing demands for data transfer, the production of components with low dielectric loss is crucial for the development of advanced antennas, which are needed to meet the requirements of next-generation communication technologies. This study investigates the impact of a variation in energy density on the part properties of a low-loss cyclic olefin copolymer (COC) in the SLS process as a way to manufacture complex low-dielectric-loss structures. Through a systematic variation in the laser energy, its impact on the part density, geometric accuracy, surface quality, and dielectric properties of the fabricated parts is assessed. This study demonstrates notable improvements in material handling and the quality of the manufactured parts while also identifying areas for further enhancement, particularly in mitigating thermo-oxidative aging. This research not only underscores the potential of COC in the realm of additive manufacturing but also sets the stage for future studies aimed at optimizing process parameters and enhancing material formulations to overcome current limitations.
CRIS-Team Scopus Importer:2024-07-12
Keywords: additive manufacturing; COC; cyclic olefine copolymer; low dielectric loss; selective laser sintering; SLS

Prozessabhängigkeit der dielektrischen Eigenschaften im FFF von COC - Romeis, Manuel; Ehrngruber, Michael; Drummer, Dietmar (Tagungsband Technomer, 2023)
Das rasante Fortschreiten der technologischen Entwicklungen in Richtung Internet der Dinge erfordert den Austausch immer größerer Datenmengen, wodurch die Anforderungen an entsprechende Antennensysteme ebenfalls weiter wächst. Durch die komplexe Formgebung und die Eröffnung komplett neuer Geometriemöglichkeiten bieten sich Additive Fertigungsverfahren für die Herstellung solch innovativer Systeme natürlicherweise an. Eine Kombination aus einem Kunststoffgrundkörper und einer Metallisierung bietet hier eine Vielzahl von dielektrischen Eigenschaften und damit Anwendungsfeldern. Ein neuartiger Ansatz bevorzugt eine Außenmetallisierung gegenüber der klassischerweise eingesetzten Innenmetallisierung, um so die Geometrievielfalt nicht durch eine benötigte Zugänglichkeit der Innenstrukturen einzuschränken und so in innovativen und neuen Designs zu denken. Da allerdings in diesem Fall das elektromagnetische Feld durch den Kunststoff geleitet wird, müssen für diesen Prozess sehr verlustarme Kunststoffe für additive Fertigungsverfahren qualifiziert werden. Ein Kunststoff mit ausgezeichneten Voraussetzungen zur Erreichung dieser Zieleigenschaften ist COC. Eingesetzt wird im Rahmen dieser Untersuchung ein kommerzielles COC Filament der Firma CREAMELT und die Verarbeitung findet auf einer OpenSource FFF-Anlage der Firma Prusa statt. Im Rahmen der gezeigten Untersuchung findet eine Evaluierung der Prozess-Bauteileigenschafts-Zusammenhänge statt. Parameter, die dabei variiert werden, sind Verarbeitungstemperatur, Schichtdicke sowie Düsendurchmesser. Speziell die Variation des Düsendurchmessers ist hierbei ein wichtiger Aspekt um in die Abmessungen der angestrebten Antennenanwendung zu gelangen. Die Ergebnisse, die hierbei charakterisiert werden ist der Einfluss auf die Bauteilabmessungen, Oberflächenrauheit, Dichte sowie die dielektrischen Eigenschaften im Bereich 20 – 50 GHz mit Hilfe eines speziell für diesen Zweck angefertigten Messresonators. Ziel ist es daraus Fertigungsrichtlinien zur Erreichung der gewünschten Eigenschaften zu erstellen.Mit reduzierter Schichthöhe und Erhöhung der Temperatur findet eine bessere Einhaltung der Sollmaße statt. Die Änderung des Düsendurchmessers zeigt keinen Einfluss in der Untersuchung der Abmessungen, allerdings eine deutliche Verbesserung der Oberflächenqualität, die Dichte wiederum fällt mit der Reduktion des Düsendurchmessers geringer aus. Ein Einfluss der Schichthöhe konnte hier nicht gezeigt werden. Bei den Messungen der dielektrischen Eigenschaften konnte eine Reduktion der relativen Permittivität sowohl mit der Erhöhung des Düsendurchmessers sowie einer Erhöhung der Temperatur und Schichtdicke gezeigt werden. Der dielektrische Verlust zeigt ebenfalls eine Reduktion mit Zunahme des Düsendurchmessers. Ein Einfluss der Temperatur sowie der Schichthöhe konnte in den Untersuchungen nicht gezeigt werden. Durch eine Bewertung von dem Zusammenspiel aus Bauteilqualität und dielektrischen Eigenschaften können so optimierte Parameter für die Fertigung von Antennenarrays abgeleitet werde